2001
DOI: 10.1007/s00421-001-0531-y
|View full text |Cite
|
Sign up to set email alerts
|

Small amounts of venous gas embolism cause delayed impairment of endothelial function and increase polymorphonuclear neutrophil infiltration

Abstract: Gas bubbles from decompression and gas embolization lead to endothelial dysfunction and mechanical injury in the pig, rabbit and lamb. In the study presented here, 0.01 ml air/min/kg was infused through a catheter into the jugular vein in 12 rabbits for 60 min. The endothelial response was measured using tension measurements in the blood vessel wall, and morphological changes where quantified using light microscopy and image processing. Percent lung water content was calculated and used to estimate the severit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
60
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(63 citation statements)
references
References 22 publications
3
60
0
Order By: Relevance
“…The body regards bubbles as foreign surfaces and responds to them some time after the gas bubbles have been formed. Rapid removal of the bubbles could prevent some of these secondary eVects (Nossum et al 1999(Nossum et al , 2002. Despite a recompression treatment, Mollerlokken et al (2007) found no signiWcant diVerence in survival time between the experimental and control groups with, however, a trend towards better survival in experimental group.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The body regards bubbles as foreign surfaces and responds to them some time after the gas bubbles have been formed. Rapid removal of the bubbles could prevent some of these secondary eVects (Nossum et al 1999(Nossum et al , 2002. Despite a recompression treatment, Mollerlokken et al (2007) found no signiWcant diVerence in survival time between the experimental and control groups with, however, a trend towards better survival in experimental group.…”
Section: Discussionmentioning
confidence: 96%
“…It was hypothesized that due to this latency before the start of treatment, the endothelial function has already been impaired to a point where recompression to 160 kPa with oxygen for 60 min has little eVect. Indeed, previous Wndings showed a relationship between gas bubbles and mechanical endothelial damage related to biochemical or immunological responses developed with time (Nossum et al 1999(Nossum et al , 2002.…”
Section: Discussionmentioning
confidence: 98%
“…DCS has been associated with endothelial dysfunction, platelet activation, occasional alterations in coagulation pathways, and rare reduction of circulating platelet counts (2, 18 -20). Neutrophil activation and perivascular adherence are associated with functional deficits postdecompression in animal models (14,17). DCS is a risk associated with deep-sea SCUBA diving, high-altitude aviation, and space exploration.…”
mentioning
confidence: 99%
“…Small amounts of venous gas emboli (VGE) lead to impaired endothelial function and increases polymorphonuclear leukocyte (PMN) infiltration in the lung (Nossum et al 2002). Intravascular gas bubbles develop in the venous system during decompression (Brubakk et al 1986;Eckenhoff et al 1990), following laparoscopy, by accidental injection and during cardiopulmonary bypass (Johnston et al 1993;Hoka et al 1997;Webb et al 1997) and may lead to endothelial damage (Warren et al 1973;Philp 1974;Nossum et al 1999).…”
Section: Introductionmentioning
confidence: 97%
“…gas bubbles, we evaluated whether i.v. injection of a monoclonal antibody (MAb) against C5a affects endothelial dysfunction and pulmonary PMN infiltration caused by low-grade VGE (Nossum et al 2002).…”
Section: Introductionmentioning
confidence: 99%